Malaysian primipara's knowledge and practice on newborn care during the postnatal period - A. Aziz, Nazura; Lee, Khuan (Community Health Society Malaysia, 2014)
Background: Inadequate knowledge and practice among primipara in caring of newborn, especially during the early period at home may cause newborn morbidity and mortality. The aim of this study was to determine the knowledge and practice among primipara mothers in taking care of a newborn during the postnatal period. Materials and Methods: A cross-sectional study design and systematic random sampling methods were used in this study. The data were collected from January until March 2013 at two community health clinics in a district of Selangor, Malaysia. The inclusion criteria were postnatal primipara mothers who visited the maternity and child clinics for their first postnatal follow-up. A pre-tested self-administered questionnaire was designed to capture specific knowledge and practice. Result: The mean age of the 162 respondents was 27.7 years. There was a significant association between the knowledge and practice of respondents in exclusive breastfeeding (P < 0.05); detection and care of jaundice (P < 0.05); ensuring the newborn is kept warm (P < 0.05) and care of physical hygiene (P <0.05). The main sources of information concerning how to take care of a newborn were 53.1% from family members, 29.6% from nurses’ home visits, and 26.5% from the media. Conclusion: This study revealed a gap in the knowledge and practice of respondents in exclusive breastfeeding, the danger of sunning a jaundiced newborn, bathing, eye care and the umbilical cord care. A revision of the current content of antenatal health education should be undertaken systematically to supplement the gap in newborn care.